Insight into Interaction Mechanism of the Inhibitor pDI6W with MDM2 Based on Molecular Dynamics (Journal of Atomic and Molecular Sciences, 2013)
The p53-MDM2 interaction has been an important target of drug design curing cancers. In this work, Molecular dynamics (MD) simulation coupled with molecular mechanics/Poisson Boltzmann surface area method (MM-PBSA) is performed tocalculate binding free energy of peptide inhibitor pDI6W to MDM2. The results showthat van der Waals energy is the dominant factor of the pDI6W-MDM2 interaction.Cross-correlation matrix calculated suggests that the main motion of the residues inMMDM2 induced by the inhibitor binding is anti-correlation motion. The calculationsof residue-residue interactions between pDI6W and MDM2 not only prove that fiveresidues Phe19’, Trp22’, Trp23’, Leu26’ and Thr27’ from pDI6W can produce strong interactions with MDM2, but also show that $CH$-$π,$ $CH$-$CH$ and $π$−$π$ interactions drivethe binding of pDI6W in the hydrophobic cleft of MDM2. This study can provide theoretical helps for anti-cancer drug designs.